Еnvironmental literacy of students in Belgrade schools: Results of a Pilot Research - Мilica V. Marušić Jablanović; Јеlena M. Stanišić; Slađana D. Savić (University of Belgrade, Teacher Education Faculty, 2023)
The environmental issues that our country is faced with are numerous, while the consequences of environmental degradation affect the health and the quality of life of our citizens. In this context, the issue of environmental education and environmental literacy is gaining momentum. In the present pilot research we examined the possibility of applying an international instrument for determining the level of environmental literacy, the Middle School Environmental Literacy Survey (MSELS), on a population of students in the higher grades of elementary school in Serbia. This instrument measures the environmental literacy using four components: environmental knolwedge, environmental affect, cognitive skills, and environmental behavior, together with corresponding sub-components. The content of the instrument was analyzed in the context of Biology and Civic education curricula as well as educational standards for the end of compulsory education for the subject Biology. Survey method was used in the research, while the data were analyzed using descriptive statistics. The data were collected on a sample of the seventh-grade elementary school students (N=111) from the territory of Belgrade. In addition, five group interviews were conducted with the students to check the clarity of the content of the instrument. The researchers established that the implementation of this instrument is adequate on several grounds: 1) the instrument is well-grounded in theory; 2) the instrument is based on a comprehensive approach to environmental literacy measurement; 3) the instrument is adequate in terms of the teaching and learning program in our education system and 4) the instrument has solid metric features. An overall reliability of the instrument is ,87. The respondents had the highest score in the component of affective attitudes towards environment, relative to other measured components, as well as relative to two countries used for comparing the results (USA, Greece). The lowest score was identified on the scale of the basic environmental knowledge, and the conclusion is that students did not fully master the knowledge envisaged in the educational standards for Biology lessons. The main disadvantage of the instrument is the time required for filling it out due to the amount of the content.